2015
DOI: 10.1007/s10238-015-0347-4
|View full text |Cite
|
Sign up to set email alerts
|

Severity of non-alcoholic fatty liver disease is associated with high systemic levels of tumor necrosis factor alpha and low serum interleukin 10 in morbidly obese patients

Abstract: Morbid obesity has been shown to increase the risk to develop hepatic steatosis, also referred to as non-alcoholic fatty liver disease (NAFLD). Emerging evidence suggests that the severity of NAFLD may associate with increased serum levels of inflammatory markers as well as decreased concentration of mediators with anti-inflammatory actions, such as tumor necrosis factor alpha (TNF-α) and interleukin (IL) 10, respectively. We thus examined the serum levels of TNF-α and IL-10 in 102 morbidly obese women and men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 60 publications
4
41
1
1
Order By: Relevance
“…Other studies have shown in parallel that the reduction, dysfunction, or disproportionate number of Treg cells contributes to the progression to NASH because Treg cells play a critical role in regulating the inflammatory processes in the liver (24, 29, 30). This cellular imbalance is accompanied by the activation of the IL-17 axis, and an increase of other pro-inflammatory cytokines such as IL-6, and TNF-α (42, 58); and its value has been highlighted by the demonstration that therapies targeted to reverse this imbalance have shown the potential to alleviate steatosis and the progression to NASH (32, 61, 62). …”
Section: The Role Of Cellular Immune Imbalances In Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have shown in parallel that the reduction, dysfunction, or disproportionate number of Treg cells contributes to the progression to NASH because Treg cells play a critical role in regulating the inflammatory processes in the liver (24, 29, 30). This cellular imbalance is accompanied by the activation of the IL-17 axis, and an increase of other pro-inflammatory cytokines such as IL-6, and TNF-α (42, 58); and its value has been highlighted by the demonstration that therapies targeted to reverse this imbalance have shown the potential to alleviate steatosis and the progression to NASH (32, 61, 62). …”
Section: The Role Of Cellular Immune Imbalances In Nafldmentioning
confidence: 99%
“…The NAFLD immune imbalances, in addition to the above, appears to be also associated with deficient synthesis or release of anti-inflammatory and antifibrotic cytokines as IL-10 (58, 61), IL-4 (61, 123), IL-22 (42), and interferon gamma (IFN-γ) (124) that have a protective effect by suppressing the maturation of Th17 cells or counterbalancing the IL-17 effects (42, 61, 125127). For example, Treg requires IL-10 signaling to suppress the Th17 cell-mediated inflammation (100), and this anti-inflammatory cytokine was decreased in morbidly obese patients with NAFLD (58).…”
Section: Underlying Mechanisms Pathways and Relationship Between Cementioning
confidence: 99%
See 1 more Smart Citation
“…En este contexto, se ha demostrado que los pacientes con hiperuricemia asintomática tienen valores elevados de marcadores proinflamatorios, incluyendo IL-6, IL-1 beta e IL-18 4,6 . Sin embargo, hasta la fecha se desconoce si el AU guarda la misma relación con marcadores proinflamatorios y antiinflamatorios en la población mexicana, y si esta relación está vinculada con otras alteraciones metabólicas, así como con un mayor riesgo de desarrollar hipertensión arterial sistémica, DM2, SMet y EHGNA [19][20][21][22][23][24] .…”
Section: Introductionunclassified
“…TNF could bind to trimerized TNF receptor type I and activate NF-B via the inhibitor of the nuclear factor kappa-B kinase (IKK) pathway. TNF- could induce c-Jun N-terminal kinase (JNK) activation, which is associated with the induction of hepatocyte death (31,32). On the other hand, Lv and his colleagues (33) found that TNF- could directly induce lipid accumulation through the AMP-activated protein kinase (AMPK) pathway, which is known as an important factor in the process of energy homeostasis.…”
Section: Ppar Agonists and Inflammation In Nafldmentioning
confidence: 99%